The Effectiveness of Learning Platforms on Students' 6C Skills of Elementary School Students - Lailatun Najmiah; Fasihah Abidah binti Anoar (LEOTECH: Journal of Learning Education and Technology, 2026)
This study examines the effectiveness of digital learning platforms in supporting the development of elementary school students’ 6C skills, including critical thinking, creativity, collaboration, communication, citizenship, and character. Using a quantitative descriptive approach, data were collected from 382 students through 6C skills tests and questionnaires measuring students’ perceptions of platform effectiveness. The data were analyzed using descriptive statistics, Pearson correlation, and one-way ANOVA to identify patterns and differences across schools. The results indicate a positive and significant relationship between the use of digital learning platforms and students’ 6C skills, although the correlation strength is relatively low and varies between schools. These findings indicate that digital platforms contribute modestly to the development of students’ 6C skills and that their effectiveness largely depends on pedagogical implementation and school readiness.